Piotroski, Graham and Greenblatt: an Empirical Approach to Value Investing in the Brazilian Stock Market - Carlos Henrique Souza Domingues; Alexandre Aronne; Francisco Pereira; Frank Magalhães (BBR: Brazilian Business Review)
In this paper, multifactor asset pricing models are used to assess and compare the performance - through the analysis of Jensen’s alpha - of three equity portfolios constructed according to the value investing strategies proposed by Joseph Piotroski, Benjamin Graham, and Joel Greenblatt. Three portfolios are constructed according to the methodologies developed by each author, using financial and accounting data from a sample of 598 stocks traded in the Brazilian stock exchange during the period Jan/2006-Dec/2019. Parameters of a five-factor model - an extended version of Carhart’s four factor model with the inclusion of an illiquidity factor - are estimated for each of the three portfolios. Regression results indicate that the three strategies have generated positive and statistically significant Jensen’s alpha in the five-factor model setting and other variations. However, the excess returns estimated according to different specifications vary substantially. The Capital Asset Pricing Model specification seems to underestimate Jensen’s alpha when compared to other specifications that provide higher explanatory power (adjusted R2).